Data analysis methods in physical oceanography - Emery, William J. (Elsevier, 2004)
Data acquisition and recording -- Introduction -- Basic sampling requirements -- Temperature -- Salinity -- Depth or pressure -- Sea-level measurement -- Eulerian currents -- Lagrangian current measurements -- Wind -- Precipitation -- Chemical tracers -- Transient chemical tracers -- Data processing and presentation -- Introduction -- Calibration -- Interpolation -- Data presentation -- Statistical methods and error handling -- Sample distributions -- Probability -- Moments and expected values -- Common probability density functions -- Central limit theorem. Estimation -- Confidence intervals -- Slecting the sample size -- Confidence intervals for altimeter bias estimates -- Stimation methods -- Linear estimation (regression) -- Relationship between regression and correlation -- Hypothesis testing -- Effective degrees of freedom -- Editing and despiking techniques: the nature of errors -- Interpolation: filling the data gaps -- Covariance and the covariance matrix -- Bootstrap and jackknife methods -- The spatial analyses of data fields -- Traditional block and bulk averaging -- Objective analysis -- Empirical orthogonal functions -- Normal mode analysis -- Inverse methods -- Time-series analysis methods -- Basic concepts -- Stochastic processes and stationarity -- Correlation functions -- Fourier analysis -- Harmonic analysis -- Spectral analysis -- Spectral analysis (parametric methods) -- Cross-spectral analysis -- Wavelet analysis -- Digital filters -- Fractals.